2000
DOI: 10.1530/eje.0.1420683
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive adrenomedullin (AM) concentration in maternal plasma during human pregnancy and AM expression in placenta

Abstract: Adrenomedullin (AM) is a novel vasorelaxant peptide, isolated from human pheochromocytoma. Although AM may be involved in the regulation of the cardiovascular system, a number of other mechanisms are also involved. The present study was undertaken to confirm the presence of AM in human maternal circulation and in placental function during pregnancy. Immunoreactive (ir) AM concentrations in maternal plasma were 3.4 Ϯ 0.7 fmol/ml (mean Ϯ S.E.M.) in the first trimester, 3.3 Ϯ 1.1 fmol/ml in the second trimester, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Yet one of the greatest increases in plasma AM levels occurs during the course of a normal pregnancy, when plasma levels of the peptide, secreted by the placenta, are 4- to 5-fold higher by the third trimester (21,(29)(30)(31)(32) and rapidly return to pre-pregnancy values after delivery (21). As recently reviewed by Wilson et al and Di Iorio et al, numerous clinical studies have attempted to correlate altered AM levels with a variety of pregnancy complications, including preeclampsia, spontaneous abortion, gestational diabetes, and FGR (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…Yet one of the greatest increases in plasma AM levels occurs during the course of a normal pregnancy, when plasma levels of the peptide, secreted by the placenta, are 4- to 5-fold higher by the third trimester (21,(29)(30)(31)(32) and rapidly return to pre-pregnancy values after delivery (21). As recently reviewed by Wilson et al and Di Iorio et al, numerous clinical studies have attempted to correlate altered AM levels with a variety of pregnancy complications, including preeclampsia, spontaneous abortion, gestational diabetes, and FGR (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 We and others have shown a progressive increase in maternal plasma ADM levels throughout pregnancy. [11][12][13][14][15][16] In PE, early reports suggested that maternal ADM levels were decreased, but subsequent larger series found no difference from controls. 14,17,18 However, we believe that this indicates a lack of compensatory increase in response to the hypertensive state.…”
mentioning
confidence: 99%
“…Different research groups have shown elevated levels of AM in plasma of pregnant women at term (from 3-to 5-fold increase), as compared to levels in non-pregnant women or levels in the early puerperium Kanenishi et al, 2001;Kobayashi et al, 2000). Other vasoactive substances, such as endothelin, prostaglandin E2, and prostacyclin, have also been reported to increase in maternal plasma in a similar fashion (Brennecke et al, 1985;Goodman et al, 1982;Mastrogiannis et al, 1991).…”
Section: Clinical Aspects Related To the Levels Of Am In Normal Pregnmentioning
confidence: 92%
“…Occasionally, immunocytochemical staining for AM has also been reported in cytotrophoblast cells and in the mesenchyma and inflammatory cells within the villi (Kanenishi et al, 2001;Macri et al, 1998). The fetal membranes, and, more specifically, the epithelium of the amniotic membrane, also show high levels of AM and its mRNA (Kanenishi et al, 2000(Kanenishi et al, , 2001Kobayashi et al, 2000;Macri et al, 1996b;Makino et al, 1999c). The pattern and intensity of AM immunoreactivity in the first trimester human placenta and fetal membranes were reported to be similar to that in term pregnancy (Macri et al, 1996a;Kanenishi et al, 2001), suggesting that AM secreted from these sites might play an important role in the maintenance of normal pregnancy throughout gestation.…”
Section: Am In Early Developmental Stages Am In Fetoplacental Tissuesmentioning
confidence: 96%
See 1 more Smart Citation